Literacy Strengthening as Character Education through Mamaca Tradition of Madurese Community in Sumenep - Agustina Dewi; Akhmad Sofyan; Panakajaya Panakajaya; Dewi Angelina (The Faculty of Teacher Training and Education The University of Jember Jember, Indonesia, 2019)
Mamaca belongs to the tradition of Madurese community in which it is conducted by singing the poetry text. This explanation ensures that mamaca uses a beautiful language. The stories contained in mamaca text are very diverse, some are taken from babad story, the stories of the prophets, the stories of historical figures, and fictional stories or figures containing petotor or advices. Based on the diverse contents written on the texts, it makes mamaca plays an important role in the existence and influence on oral mamaca tradition in Madurese community. Its existence in the community is done by strengthening the literacy through mamaca. Literacy strengthening through mamaca was expected to become a medium in strengthening the character of Madurese community, especially by delivering the religious values. Qualitative method was applied in this reserach to understand a social phenomenon holistically (as a whole). This qualitative method allowed us to understand and view people as they expressed their views of themselves.